Comprehensive analysis of mycobacterium tuberculosis antigen-specific CD4+ T cell responses restricted by single HLA class II allotype in an individual - Lee, Yong-Hun; Hyun, You-Seok; Jo, Hyeong-A; Baek, In-Cheol; Kim, Sun-Mi; Sohn, Hyun-Jung; Kim, Tai-Gyu (Frontiers in Immunology, 2022)
Mycobacterium tuberculosis infection is generally asymptomatic as latent tuberculosis, but it is still known as the world's leading bacterial cause of death. The diagnosis of latent tuberculosis infection relies on the evidence of cellular immunity to mycobacterial antigens. Since the association between HLA class II and tuberculosis infection has been reported in several population groups, a detailed study on the CD4+ T cell response to major tuberculosis antigens is needed. To elucidate which HLA class II allotypes in an individual are preferentially used in tuberculosis, CD4+ T cells specific to TB10.4, Ag85b, ESAT-6, and CFP-10 of Mycobacterium tuberculosis antigens were analyzed comprehensively. A total of 33 healthy donors were analyzed by ex vivo and cultured ELISPOT using panels of artificial antigen-presenting cells expressing a single HLA class II allotype. The CD4+ T cell responses were increased by an average of 39-fold in cultured ELISPOT compared with ex vivo ELISPOT. In ex vivo and cultured ELISPOT, CD4+ T cell responses showed significantly higher by HLA-DR than those of HLA-DQ and HLA-DP locus. In cultured ELISPOT, 9 HLA-DR allotypes, 4 HLA-DQ allotypes, and 3 HLA-DP allotypes showed positive CD4+ T cell responses. Among ten donors with positive CD4+ T cell responses when tested for mixed Mycobacterium tuberculosis antigens, seven donors were positive for only a single allotype, and three were positive for two allotypes in an individual. However, only one allotype was used for a single antigen-specific response when a single tuberculosis antigen was used individually. These results on the distribution of HLA class II allotypes showing high CD4+ T-cell responses to Mycobacterium tuberculosis antigens and the intra-individual allotype dominance will provide valuable information for understanding the immunobiology and immunogenetics of tuberculosis, which can contribute to the development of more effective vaccines.